2018
DOI: 10.1371/journal.pone.0201375
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from an acute systemic and central LPS-inflammation challenge is affected by mouse sex and genetic background

Abstract: Genetic and sexual factors influence the prevalence and the pathogenesis of many inflammatory disorders. In this study their relevance on the peripheral and central inflammatory status induced by a peripheral injection of lipopolysaccharide (LPS) was evaluated. BALB/c and CD-1 male and female mice were intraperitoneally injected with LPS. Spleens and brains were collected 2 and 72 hours later to study the levels of IL-6, TNF-α and IL-1β. Percentage of microglia and astrocytes was determined in the cortex and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Our study differed from these previous reports as we utilized: (a) a different dose of LPS; (b) mice of both sexes; and (c) transgenic mice on a mixed genetic background. As the effects of systemic LPS on microglia activation in mice are dependent on genetic background and sex (Meneses et al, ), these factors may explain the differences between these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our study differed from these previous reports as we utilized: (a) a different dose of LPS; (b) mice of both sexes; and (c) transgenic mice on a mixed genetic background. As the effects of systemic LPS on microglia activation in mice are dependent on genetic background and sex (Meneses et al, ), these factors may explain the differences between these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we wondered how the cytokine profile in response to 40 Hz flicker differed from acute inflammation. Thus, we assessed cytokine expression in the visual cortex of animals intraperitoneally injected with LPS, a traditional, acute model of inflammation (Gabellec et al, 1995;Qin et al, 2007;Meneses et al, 2018). As in our flicker experiments, we characterized cytokine expression in visual cortex of mice injected with LPS versus vehicle injection and separated these differences using a PLSDA (Fig.…”
Section: Hz Flicker Induces Neuroimmune Profile Distinct From Acute Imentioning
confidence: 99%
“…Prior sepsis alters the responsivity of the circadian system to subsequent immune challenges. LPS-induced sepsis shapes the response to subsequent administration of lower dosages of LPS in mice (Meneses et al, 2018). Testing the responsiveness of the circadian system of mice to LPS showed that while in control animals LPS induced a significant phase delay of the behavioral rhythm, it did not occur in post-septic animals (Castanon-Cervantes et al, 2010).…”
Section: The Circadian Rhythm Plays a Role In The Pathogenesis Of Sepsismentioning
confidence: 99%